The effect of weaning age on the reproductive performance of Nellore cows raised in native and jaraguá pastures - Aroeira, José A. D. C.; Rosa, Antonio do N.; Verneque, Rui da S. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to evaluate the effect of three different weaning ages on the calving intervals (CI) of Nellore cows. It was carried out from July 1977 through July 1982 and envolved two groups of 51 cows, one in a Jaraguá pasture (Hyparrhenia rufa) and the other in a native pasture. The calves in each herd were weaned at three, five and seven months of age. The CI estimated overall mean was 422 ± 5 days. Year of parturition, pasture, parturition order, season of conception and weaning age had significant (P < 0.05) effects on Cl. The CI was higher in native (434 days) than in Jaraguá pasture (411 days). There were no differences among CI of cows from 2nd through 7th parturition order. The increased CI up to 7th parturition order was associated with poor body conditions of older cows. The effects of season of conception on calving intervals were discussed based on the related season of parturition. The shortest CI (393 days) was observed on cows calving from September through December. The CI of cows that weaned calves with seven months of age (448 days) was longer than those whose calves were weaned at five (414 days) and three months (406 days)- This result probably is associated with more favorable pre-partum weight gain variations.